El nuevo potro indomable: El problemático estándar de motivación de los laudos exigido por las cortes peruanas - Cantuarias Salaverry, Fernando; Repetto Deville, José Luis (Pontificia Universidad Católica del Perú, 2015)
The author makes a critical analysis of the current situation of the Arbitration in Peru, from various court decisions that have identified the standard of motivation that must have an arbitration award. In this way, the author indicates that the consequences of annulling arbitral awards by improper motivation, insufficient motivation or follow criteria of the Arbitral Tribunal are severe and it affects all the progress that has been obtained in the arbitration in these last two decades.

El autor hace un análisis crítico la situación actual del Arbitraje en el Perú, a partir de diversas decisiones de las cortes al momento de identificar el estándar de la motivación que debe tener un laudo arbitral. De esta forma, precisa que las consecuencias de anular laudos arbitrales por indebida motivación, insuficiente motivación o por calificar criterios del Tribunal Arbitral son graves y afecta todo el avance que se ha obtenido en el Arbitraje en estas dos últimas décadas.
The new indomitable colt: The problematic standard of motivation of awards required by Peruvian courts
Keywords: Arbitration; Awards; Motivation; Arbitration Tribunal; Uncitral Model Law; General Arbitration Law; Arbitraje; Laudos; Motivación; Tribunal Arbitral; Ley Modelo de Uncitral; Ley General de Arbitraje; https://purl.org/pe-repo/ocde/ford#5.05.00